Multi-site-mediated entwining of the linear WIR-motif around WIPI β-propellers for autophagy - Jinqi Ren (Nature Portfolio, 2020)
WIPI proteins are mammalian PROPPIN family phosphoinositide effectors that recognize a WIPI-interacting-region (WIR)-motif to recruit other regulators during autophagosome formation. Here, the authors combine structural and functional studies and present the crystal structure of human WIPI3 with a bound ATG2A WIR-peptide and observe that the WIR-motif binds to three sites in blades 1-3 of WIPI3 and mutating these binding sites impairs the ATG2A-mediated autophagic process.